THE IMPACT OF SOCIAL MEDIA ON THE MENTAL HEALTH OF YOUNG PEOPLE - Berdiqulova Mahbuba Erkinjon qizi; Nurboyeva Pokiza Erkinjon qizi (TADQIQOTLAR, 2026)
In the modern digital era, social media has become an essential part of everyday life, especially for young people. Platforms such as Instagram, TikTok, and Facebook allow individuals to communicate, share information, and express their thoughts. Although social media provides many opportunities for connection and learning, researchers are increasingly concerned about its psychological effects. This article explores the impact of social media on the mental health of young people, discussing both positive and negative consequences, as well as strategies for maintaining a healthy digital lifestyle.